Amyloplast Membrane Protein SUBSTANDARD STARCH GRAIN6 Controls Starch Grain Size in Rice Endosperm. Issue 3 (20th January 2016) - Matsushima, Ryo; Maekawa, Masahiko; Kusano, Miyako; Tomita, Katsura; Kondo, Hideki; Nishimura, Hideki; Crofts, Naoko; Fujita, Naoko; Sakamoto, Wataru
Abstract : Starch grain size is an important factor for industrial applications of starch and is affected by a novel amyloplast membrane protein. Abstract: Starch is a biologically and commercially important polymer of glucose. Starch is organized into starch grains (SG s) inside amyloplasts. The SG size differs depending on the plant species and is one of the most important factors for industrial applications of starch. There is limited information on genetic factors regulating SG sizes. In this study, we report the rice ( Oryza sativa ) mutant substandard starch grain6 ( ssg6 ), which develops enlarged SG s in endosperm. Enlarged SG s are observed starting at 3 d after flowering. During endosperm development, a number of smaller SG s appear and coexist with enlarged SG s in the same cells. The ssg6 mutation also affects SG morphologies in pollen. The SSG6 gene was identified by map-based cloning and microarray analysis. SSG6 encodes a protein homologous to aminotransferase. SSG6 differs from other rice homologs in that it has a transmembrane domain. SSG6-green fluorescent protein is localized in the amyloplast membrane surrounding SG s in rice endosperm, pollen, and pericarp. The results of this study suggest that SSG6 is a novel protein that controls SG size. SSG6 will be a useful molecular tool for future starch breeding and applications.